The Influence Of School Principal Management On Increasing Digital-Based Teachers' Capability In Min City Of Banda Aceh - Safranovi Safranovi; Nasir Usman; Murniati AR (STKIP Singkawang, 2024)
Digital-based teacher capabilities have a very important role in the current modern educational context. With the rapid development of technology, the integration of technology in learning has become a necessity. Various methods or programs are needed to improve digital-based teacher skills. This research aims to determine the influence of school principal management on increasing digital-based teacher capabilities. The research method used is an experimental method with a one group pretest-posttest design. The subjects in this study consisted of 8 people each, 2 school principals and 2 head of curriculum, 2 supervisors and 2 teachers from each school who were taken using saturated sampling techniques. Data collection techniques in this research used interviews, questionnaires and test results. The data analysis technique used uses a qualitative and quantitative approach. The results of the T test show a significance value of 0.002 <0.05, which shows that there is an influence of school principal management on digital-based teacher abilities. The N-Gain Test results show a score of 70% indicating an increase in digital-based teacher abilities. Therefore, school principal management provides improvements to digital-based teacher capabilities.